ANALISIS KEBIJAKAN PAJAK DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH KABUPATEN KOLAKA TIMUR DI ERA OTONOMI DAERAH - La Ode Muhammad Elwan (Journal Publicuho, 2020)
The purpose of this study was to determine the contribution of regional taxes as a source of Original Regional Revenue, regional strategies in increasing revenue sourced from local taxes, and the status of regional independence in East Kolaka Regency in the era of regional autonomy. This research uses mixed methods with purposive sampling technique. Data collection in this research was carried out through literature studies and field studies and then analyzed descriptively quantitatively using frequency tables. The results showed that in 2016-2018 the tax did not make the slightest contribution to regional income. The strategy of East Kolaka Regency in increasing Local Revenue through local taxes is by issuing local regulations on local taxes, promoting local regulations, intensifying tax collection, imposing sanctions on taxpayers who do not obey taxes, increasing the ability of the implementing apparatus, overseeing tax management officers, optimizing updating local tax potential data and looking for potential new tax types in the region. Other findings, East Kolaka Regency cannot be said to be an autonomous region that is independent in the implementation of regional autonomy because of the low financial capacity of the region and its dependence on central assistance is still quite high.